Improved fault ride through strategy for doubly fed induction generator based wind turbines under both symmetrical and asymmetrical grid faults. Issue 8 (8th June 2016) - Mohammadi, Jafar; Afsharnia, Saeed; Vaez‐Zadeh, Sadegh; Farhangi, Shahrokh
Abstract : Due to the latest grid codes, wind turbines (WTs) are required to remain connected to grid under grid faults and supply reactive power into the grid. So, this paper proposes an improved fault ride through (FRT) strategy for doubly fed induction generators (DFIGs) under both symmetrical and asymmetrical grid faults. The proposed strategy is realized through active and passive FRT compensators. The active compensator is performed through control of the rotor‐ and grid‐side converters of DFIGs to limit the stator and rotor over currents and inject reactive power into the grid to support the grid voltage recovery, respectively. The passive compensator is based on a three‐phase rotor current limiter (RCL) resistor located in series with the rotor windings. It considerably reduces the rotor and stator overcurrent at the instants of grid faults occurrence and clearance. The proposed strategy decreases the stator and rotor over currents, electromagnetic torque oscillations and DC‐link over voltage and also support grid voltage by supplying reactive power into the grid. In this way, the DFIG can fulfill the FRT requirements of the latest grid codes. Simulation studies using MATLAB/SIMULINK are conducted on a 1.5 MW DFIG‐based WT to validate the effectiveness of the proposed FRT strategy.